Turmalinea flavicarpa sp. nov. (Boletaceae) from Asian subtropical Castanopsis forests of East China - Zhao, Yi; Huang, Jian-Feng; Peng, Hui-Fen; Lü, Jia-Qi; Liu, Le; Li, Guo-Jie; Huang, Wei-Hua (Phytotaxa, 2026)
Turmalinea flavicarpa sp. nov. (Boletaceae) is described as a new truffle species from Zhejiang Province, East China. Morphological characters of this taxon are elaborated and illustrated. It resembles the Chinese species Turmalinea chrysocarpa in its small, brightly yellow to orange basidiomata, and fusiform basidiospores with longitudinal furcate ornamentations, but differs in context odour, larger basidiospore and basidium sizes, presence of the inner layer of the peridium, and by its distribution in eastern China. Phylogenetic relationships of Turmalinea flavicarpa and other closely related species in genera Rossbeevera and Turmalinea are also analyzed based on three nuclear loci ITS-nLSU-tef-1α, two mitochondrial regions atp6-mtSSU, as well as the ITS region (excluding the minisatellite-like insertion). The novelty of the new species is supported by a combination of morphology and molecular phylogenetic analyses.